Advances in Zeolite Imidazolate Frameworks (ZIFs) Derived Bifunctional Oxygen Electrocatalysts and Their Application in Zinc–Air Batteries - Arafat, Y.; Azhar, M.R.; Zhong, Yijun; Abid, Hussein; Tadé, M.O.; Shao, Zongping (WILEY-V C H VERLAG GMBH, 2021)
Secondary Zn-air batteries (ZABs) are recognized as one of the most promising power sources for the future with lucrative features of low cost, high energy density, eco-friendliness, and high safety. However, the widespread implementation of ZABs is still hampered by the sluggish oxygen redox reactions. Thus the deployment of cost-effective and highly efficient air electrodes to substitute precious metals (Pt/Ir), is highly challenging, however, highly desired. Zeolitic imidazolate frameworks (ZIFs) are emerging functional materials, which demonstrate several outstanding characteristics, such as high specific surface area, high conductivity, self-doped N, open pore structure, versatile compositions and favourable chemical stability. Through varying the metal/organic moiety or by employing different synthesis protocols, ZIFs with different properties could be obtained. Being adaptable, desired functionalities may be further incorporated into ZIFs through pre-treatment, in situ treatment, and post treatment. Thus, ZIFs are the ideal precursors for the preparation of variety of bi-functional air electrodes for ZABs by materials tuning, morphological control, or by materials hybridization. Here, the recent advances of ZIFs-based materials are critically surveyed from the perspective of synthesis, morphology, structure and properties, and correlated with performance indicators of ZABs. Finally, the major challenges and future prospects of ZIFs associated with ZABs are discussed.